Physiotherapy Services in The Efforts of Health Services In DKI Jakarta Public Health Center - Putri Karina Syafitri; Vetty Yulianty Permanasari (Poltekkes Kemenkes Jakarta III, 2020)
The increase in non-communicable diseases such as hypertension, stroke, diabetes mellitus, joint disease, lack of physical activity, injury, and disability in line with the increasing need for physiotherapy services in health facilities, including in Public Health Centers. The role of the physiotherapist in the Public Health Centers is to carry out activities in the form of promotive and preventive without prejudice to curative and rehabilitative. The purpose of this study is to analyze physiotherapy services at the Public Health Centers using five levels of prevention measures, namely are health promotion, specific protection, early diagnosis and prompt treatment, disability limitation, and rehabilitation efforts at 6 PHC in DKI Jakarta. This study uses qualitative research methods through a phenomenological approach. The results of this study obtained a depth-overview of the efforts of health services that the provision of medical services is preferred over promotive and preventive efforts. Physiotherapy services at the PHC have been regulated in the Decree of the PHC’s Head by referring to Permenkes 75 (2014). Public health activities in collaboration with the Physiotherapy Services are only carried out by 3 PHC, and some of them only conduct individual services. This study recommends that adding one physiotherapist to be able to help physiotherapy services outside the building PHC and physiotherapy organizations can create public health training to support physiotherapy competencies.